О сингуларисном эффективном значении тока в электроцепи переменного тока с управляемыми диодами и индуктивной нагрузкой - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
By using the singularis expansion of a jump-like function, the formula for the effective current in an electrocurcuit with controlled diodes and inductance load is deduced.